Induction of buds and roots in hypocotilos and cotiledones of Physalis peruviana when 6-bencilaminopurin and 2,4-dichlorophenoxyacetic are used - Hernández-Villalobos, Karla (2020)
Physalis peruviana L. "aguaymanto" is a Solanaceae highly prized in countries such as Peru, Colombia and Ecuador due to its high nutritional value and numerous medicinal properties. Its cultivation has high variability because it is propagated by seeds, which makes it necessary to maintain its homogeneous morphological and productive characteristics. An alternative is in vitro micropropagation to subsequently achieve its technification and industrialization. Therefore, the objective of this work was to induce shoots and roots in hypocotyls and cotyledons of P. peruviana L. using auxins and cytokinins. Nine combinations were made between the concentrations of 2,4-D (0.25, 0.5 and 1.0 mg / l) and BAP (0.1, 0.25 and 1.0 mg / l), in which 20-day-old explants were introduced. The basal medium was that of Murashige & Skoog supplemented with 3% sucrose, phytagel (0.5%) and pH 6. After 70 days, after being exposed to photoperiod 16: 8, it was possible to induce callus formation in all treatments and in both types of explants. In addition, in the hypocotyls there was root induction with the 0.1 mg / l combination of 2,4-D + 1.0 mg / l of BAP and in the cotyledons roots were induced with the 0.5 mg / L combination of 2,4-D + 1.0 mg / L of BAP, and also roots and shoots in the combination 1 mg / l of 2,4-D + 1.0 mg / l of BAP. It is concluded that cotyledons favor the root / shoot regeneration process better than hypocotyls.